Emfisema Subkutis dan Simple Pneumothoraks Akibat Tenggelam; Case Report dari Rumah Sakit Tipe D - M Agung Yudistira Permana; Ni Ketut Agustiani Sudiar; AA Istri A WIda Purnama Dewi (CV. Jasa Sukses Abadi, 2020)
Drowning is defined as a condition in which acute respiratory disturbances result from immersion of the respiratory tract in a liquid, the third highest cause of death in the world. The process of holding breath can increase the pressure in the alveoli, water entering the respiratory tract will disrupt the surfactant layer, severe multi-organ complications occur, such as cardiac arrest, acute respiratory failure, lactic acidosis even a death. Early resuscitation and management are very important to support the patient's prognosis. This case report will discuss the journey and therapy of post-drowned patients in remote hospitals with limited equipment. An GS 6 years old was taken to the emergency room with a decrease in consciousness after drowning in the sea 1 hour before entering the hospital. The child had drowned for 10 minutes then helped without resuscitation and taken to the emergency room. GCS E2V1M4, HR 170x/min, RR 48x/min, temperature 38.7C and oxygen saturation 45%. During treatment, complications such as pneumothorax and massive subcutaneous emphysema occured . The treatment was done with a minimal invasive infraclavicular incisions method and obtained good results and minimal complications. Evaluation of pulmonary function and post surgical complications are needed during the healing process.